JUDICIAL ACTIVISM OR SELF-RESTRAINT : SOME INSIGHT INTO THE INDONESIAN CONSTITUTIONAL COURT - Radian Salman; Sukardi Sukardi; Mohammad Syaiful Aris (Yuridika, 2018)
The Constitutional Court of Republic of Indonesia is centralized judicial review institution which implements a posteriori and abstract control. Constitutional court decision often politically sensitive and involve important issues. On the one hand handing down strong decisions that uphold important constitutional principles can bring great benefits to citizens and can strengthen support for democracy but on the other hand, strong role of the court in judicial review tends to encroach increasingly on the territory of the law making institution. This article examines the decision of constitutional court in the framework of a tension between constitutionalism and democracy, especially from theoretical or conceptual approach. As result of examining its decisions, Indonesian Constitutional Court may reflect two characters; judicial activism as characterized by acting as law-maker and using policy in judicial decisions and/ or judicial self-restraint.  Recent  Indonesian experience shows that judicial review of legislation is not a simply of judicial control over law-making institution, as it brings  tension in the context of power relations in the scheme of separation of power. Relationship between the court and legislature, in respective of judicial review, will culminate in the philosophy of the judiciary. However, as constitutionalism and democracy are virtue, decisions of the Constitutional Court in judicial review should create mode of self-limitation within the framework of the principle of separation of powers.